Pack size in humanized landscapes: the Iberian wolf population - Fernández-Gil, Alberto; Quevedo, Mario; Barrientos, Luis M.; Nuño, Ángel; Naves, Javier; Gabriel, Miguel de; Ordiz, Andrés; Revilla, Eloy (Wildlife Biology, 2020)
Group living is an important behavioral feature in some species of mammals, although somewhat uncommon in the Order Carnivora. Wolves Canis lupus are highly social and cooperative carnivores that live in family groups, i.e. packs. The number of wolves in a pack affects social, reproductive and predatory behavior, thus conditioning population dynamics. Despite its relevance to management decisions, pack size has not been thoroughly studied in populations inhabiting human dominated landscapes such as the Iberian Peninsula. We estimated variation of wolf pack size from 1990 to 2018 in northern Spain, both in winter and summer. Winter data corresponded to direct observations and snow tracking at 42 localities (n = 253 data, 160 pack-years), whereas summer data corresponded to observations at rendezvous sites at 22 localities (n = 237 data, 43 pack-years). We estimated average pack size from the largest number of wolves recorded at each locality and year. Winter pack size averaged 4.2 ± 1.7 (mean ± SD) individuals. At summer rendezvous sites adult/subadult wolves (older than one year) averaged 3.1 ± 1.3 individuals, whereas pups averaged 4.0 ± 1.9. Generalized linear mixed models (GLMM) showed that pack size declined through the winter from 4.9 (4.2–5.6, 95% CI) wolves in November to 3.8 (2.9–4.9, 95% CI) wolves in April. We found no trend in pack size, neither in winter nor in summer. We discuss our results compared with other studies and populations worldwide, and its usefulness to comprehend the dynamics of this vulnerable population. Peer reviewed